An Ontology for Safety Assurance Information Management - Almendra, Camilo; Silva, Carla; Campelo, David (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2025: Anais do XXIV Simpósio Brasileiro de Qualidade de SoftwareDO - 10.5753/sbqs.2025.14928, 2025)
Context: Diverse information needs to be traced and managed throughout the development lifecycle of safety-critical systems, such as requirements, design definitions, tests and code. A safety-critical system (SCS) undergoes certification procedures that require the presentation of arguments supporting the design and implementation decisions involved in the SCS construction. Nowadays, many regulations require elaborating assurance cases (ACs) to present such arguments. The integrated management of the diverse data required to produce the ACs can leverage the continuous traceability assessment and support the automated generation of ACs at any time in the SCS lifecycle. Objective: Ontologies can integrate metamodels to connect data from different domains. We designed and implemented a Safety Assurance Ontology (SAO) to integrate outputs of safety and software engineering activities. SAO encompasses an information model, rules and competency questions to support the work of software, safety and assurance engineers in the context of an SCS development that requires the production of ACs. Method: SAO was built based on knowledge extracted from safety datasets and argumentation patterns. This work presents the SAO’s design, implementation, and evaluation through an illustrative scenario with public datasets and an expert survey with industrial practitioners and researchers. Results: SAO comprises concepts, relationships, and formation rules integrating safety assurance and software project information. We implemented the ontology information model and its formation rules using semantic web technologies. Conclusions: SAO can trace relevant project information, infer implicit information, and highlight traceability gaps in the public datasets evaluated. Practitioners find SAO’s competency questions on traceability gaps useful in revealing direct and indirect relationships among project items. They also find that the basic competency questions facilitate the contextualisation of items traced in the project repositories. Also, they pointed out that adding specialisations for key concepts can enhance practitioners’ grasp of the metamodel scope, thus promoting its applicability.